An analysis of the pre and post test scores and an analysis of the items on the pre and post test of a group of graduate elementary mathematics students at the University of the Philippines - Chin, Fely P.
Items in a pretest-posttest and its results when given to teacher participants in a one-semester course in math were analyzed. The methodology consists of item analysis, analysis of the performance of the group as a whole, and analysis of the performance of each participant in the tests. The pretest-posttest results generate valuable feedback not only to teachers and students but to curriculum developers as well.